Pleuroparenchymal fibroelastosis in rheumatic autoimmune diseases: a systematic literature review. (11th September 2020) - Orlandi, Martina; Landini, Nicholas; Bruni, Cosimo; Sambataro, Gianluca; Nardi, Cosimo; Bargagli, Elena; Tomassetti, Sara; Occhipinti, Mariaelena; Bellando Randone, Silvia; Guiducci, Serena; Vancheri, Carlo; Colagrande, Stefano; et al.
Abstract: Objectives: Pleuroparenchymal fibroelastosis (PPFE) is characterized by predominantly upper lobe pleural and subjacent parenchymal fibrosis; PPFE features were described in patients with rheumatic autoimmune diseases (RAID). A systematic literature review was performed to investigate the prevalence, prognosis and potential association of PPFE with previous immunosuppression in RAID. Methods: EMBASE, Web of Science and PubMed databases were questioned from inception to 1 September 2019. Articles published in English and addressing PPFE in patients with RAID were selected. Results: Twenty out of 794 papers were selected with a total of 76 cases of RAID-PPFE patients (20 SSc, 9 RA, 6 IIM6 primary SS, 5 overlap syndromes, 3 ANCA-associated vasculitides, 2 granulomatosis with polyangiitis, 1 microscopic polyangiitis, 1 UCTD, 1 SLE, 1 GCA and 21 patients with non-specified RAID). Dyspnoea was the most frequently reported symptom (37/48 patients, 77%). Patients frequently presented with a restrictive pattern and decline in diffusing lung capacity for carbon monoxide. During the follow-up, 7/12 patients had progression at imaging, 22/39 presented a generic clinical worsening, 19/38 had a functional deterioration and 15/43 remained stable. Conclusion: The present systematic literature review confirms that PPFE features are present in RAID. Rheumatologists should be aware of this new radiological pattern that holds a bad prognosis.